Corpo e gestualidade :o jogo da capoeira e os jogos do conhecimento - Dias, João Carlos Neves de Souza e Nunes (2007)
In the direction of questing a sociology that considers the flesh dimension of the existence, that favors to think the body while place of the production of the knowledge, our itinerary of research is characterized for the reflection on the gesture of the body as power of life and production of knowledge, recognizing the precision of the gesture as a privileged breach of comment of the collective life, of the projection and registration of the culture, of the symbolic, of the sensitivity. Our problematic can be meet in the possibility to enhance an open and sensible rationality, tattooed in the body and accessible for the gestures, that its materialized in the relations of the human being with the other and the world, in singular and collective relations. Therefore, the gesture, constructed in the intention the experience of the body, can tell us about the human being, the society and the culture, therefore the sensed of the gestures is constructed from the established and recognized mutual actions for the citizens. It is in this field of production of the knowledge, of knowing of the meat that we direct our perception, in the challenge to immerge into the intention of the gesture in the capoeira game. Of the methodological point of view, for the analysis of the gestures of the capoeira, therefore, of the body as knowledge power, we consider registers of images as well as narratives registers of the universe of the capoeira, as well as my experience of more than seven years in the group of capoeira cordão de ouro1. A epistemological exercise has as support a qualitative research where parts of the quantity of images of the investigated group, as well as interviews, daily registers in of field and over all my experience of life next to the group and to the capoeira, in intention to recognize symbols tattooed in the body and for it produced in the inter subjectivists relations. We search therefore, to evidence sensible and meanings drawn for the gesture and evidenced by the look of the researcher. We presents as objectives of this inquiry to nuance ribbings around of the social and cultural elements in the production of the knowledge of the body, of the gesture, weaveeed for the sensible rationality